Pollutant Dispersion in Built Environment - Ming, Tingzhen; Peng, Chong; Gong, Tingrui; Li, Zhengtong (Springer Nature Singapore : Imprint: Springer, 2017)
This book discusses energy transfer, fluid flow and pollution in built environments. It provides a comprehensive overview of the highly detailed fundamental theories as well as the technologies used and the application of heat and mass transfer and fluid flow in built environments, with a focus on the mathematical models and computational and experimental methods. It is a valuable resource for researchers in the fields of buildings and environment, heat transfer and global warming.